Bountiful Harvest - Mekwunye, Stephanie (Evans Brothers (Nigeria Publishers) Ltd, 2012)
The villages of Unuofia and Owu have their big losses after the war, but the losses of Owu are bigger in proportion than expected. While Umuofia now progresses, Owu steadily declines. The people are in great distress and discomfort$1! =s
Keywords: Folktales